Kedudukan Hukum Administrasi Negara Dalam Ilmu Hukum - I Nyoman Artayasa (Jurnal Ilmiah Cakrawarti, 2019)
State Administrative Law is the Law regarding the Government / Executive inits position, duties, functions and authority as a State Administrator. State AdministrativeLaw is one branch / part of specialized legal science. State Administrative Law is a legalscience that is not static, but develops according to the development of needs in society.In public law, at first State Administrative Law is part of the State Law, lectures on StateAdministrative Law are embedded in the State Law. The function of State AdministrativeLaw, namely: Ensuring Legal Certainty. Guaranteeing Legal Justice. Administrative LawWorks As A Guide and Size.